Terms, definitions and measurements to describe sonographic features of lymph nodes: consensus opinion from the Vulvar International Tumor Analysis (VITA) group - Fischerova, D; Garganese, G; Reina, H; Fragomeni, S M; Cibula, D; Nanka, O; Rettenbacher, T; Testa, A C; Epstein, E; Guiggi, I; Frühauf, F; Manegold, G; et al. (Ultrasound in obstetrics & gynecology, 2021)
In centers with access to high-end ultrasound machines and expert sonologists, ultrasound is used to detect metastases in regional lymph nodes from melanoma, breast cancer and vulvar cancer. There is, as yet, no international consensus on ultrasound assessment of lymph nodes in any disease or medical condition. The lack of standardized ultrasound nomenclature to describe lymph nodes makes it difficult to compare results from different ultrasound studies and to find reliable ultrasound features for distinguishing non-infiltrated lymph nodes from lymph nodes infiltrated by cancer or lymphoma cells. The Vulvar International Tumor Analysis (VITA) collaborative group consists of gynecologists, gynecologic oncologists and radiologists with expertise in gynecologic cancer, particularly in the ultrasound staging and treatment of vulvar cancer. The work herein is a consensus opinion on terms, definitions and measurements which may be used to describe inguinal lymph nodes on grayscale and color/power Doppler ultrasound. The proposed nomenclature need not be limited to the description of inguinal lymph nodes as part of vulvar cancer staging; it can be used to describe peripheral lymph nodes in general, as well as non-peripheral (i.e. parietal or visceral) lymph nodes if these can be visualized clearly. The association between the ultrasound features described here and histopathological diagnosis has not yet been established. VITA terms and definitions lay the foundations for prospective studies aiming to identify ultrasound features typical of metastases and other pathology in lymph nodes and studies to elucidate the role of ultrasound in staging of vulvar and other malignancies. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.
Keywords: směrnice pro lékařskou praxi jako téma; ultrasonography; Societies, Medical; gynekologie; Practice Guidelines as Topic; lidé; Gynecology; lymfatické metastázy; lymph nodes; společnosti lékařské; groin; Lymphatic Metastasis; ultrasonografie; ženské pohlaví; Humans; diagnostic imaging; Ultrasonography; vulvar neoplasm; Female; Vulvar Neoplasms; nádory vulvy